Innovation and growth in regions with specific geographical features - Juliana Dahl (Kiel Institute for the World Economy (IfW), 2013)
Since the year 2000, innovation and the path towards a knowledge-based economy have become prominent concepts in the European policy sphere. Although fostered by the goal of the innovationoriented Lisbon Strategy, it remains questionable in how far the situation of being the most competitive economy favours the diverse territories in the European Union. In this matter, very little is known about the ability to translate innovation into regional growth in territories with geographical disadvantages. The present paper discusses the intensified emphasis of the European policy approach towards innovation and its adequacy to the need of regions with unfavourable geographical features. This thorough discussion aims to shed some light on the issue of whether the EU's twin goals for 2007-2013, to achieve global competitiveness and cohesion, are suitable for areas with geographical limitations.
Keywords: 330; European Regional Development Fund; Innovation; Regional Policy; Specific Geographical Features